2022
DOI: 10.1038/s41598-022-11090-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of miR-17-5p and miR-20a-5p predicts favorable disease-specific survival in stage I-III colon cancer

Abstract: In many types of cancer, microRNAs (miRs) are aberrantly expressed. The aim of this study was to explore the prognostic impact of miR-17-5p and miR-20a-5p in colon cancer. Tumor tissue from 452 stage I-III colon cancer patients was retrospectively collected and tissue microarrays constructed. miR-17-5p and miR-20a-5p expression was evaluated by in situ hybridization and analyzed using digital pathology. Cell line experiments, using HT-29 and CACO-2, were performed to assess the effect of miR-17-5p and miR-20a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…On the other hand, higher expression levels of miR-19a-3p and miR-20a-5p were observed in the low-risk group. That is in agreement with the results of Selven et al who showed a favorable prognosis for colorectal cancer patients with high miR-20a-5p expression [ 33 ]. Similarly, Farzadfard et al reported higher circulating miR-19a-3p in CLL patients than in healthy subjects [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, higher expression levels of miR-19a-3p and miR-20a-5p were observed in the low-risk group. That is in agreement with the results of Selven et al who showed a favorable prognosis for colorectal cancer patients with high miR-20a-5p expression [ 33 ]. Similarly, Farzadfard et al reported higher circulating miR-19a-3p in CLL patients than in healthy subjects [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also demonstrated higher miR-20a-5p and miR-92a-1-5p expression levels in CLL patients with CR and/or PR than in patients who died. The results of the current study are consistent with those of Selven et al that have shown that high expression levels of miR-20a-5p in tumor tissue are independent indicators of favorable disease-specific survival in colon cancer [ 33 ]. Likewise, Papageorgiou et al reported that high miR-92a-3p expression predicts significantly prolonged OS (overall survival) of CLL patients [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…1 ). Consistent with our results, Selven et al also demonstrated that high expression levels of miR-20a-5p are positively correlated with a favorable prognosis in advanced stages of CRC [ 37 ]. Additionally, miR-122-5p has been identified to promote CRC progression [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…The higher expression of these miRNAs also correlated with negative ZAP70 and CD38 expression, while low miR-20a expression (<1.629) was strongly associated with shorter time to treatment (TTT) and PD. In multivariate analysis, low miR-20a expression remained an independent marker predicting short TTT for CLL patients, replying to the results obtained by Selven and colleagues [81] in colorectal cancer and opening a way to its use as a potential blood biomarker.…”
Section: Mir-17-92 Clustermentioning
confidence: 68%